(untitled) (International Conference on Computers in Education, 2022)
Learning Analytics research provides findings and analytical methods. However, those have not been frequently shared and reused in other studies. The objective of this study is to clarify the possibilities and challenges in applying a behavioral analysis method to other system contexts. This study uses the Evaluation Behavior Analysis (EBA) as an example of an analytical method, and compared the applicability of the method and reproducibility of findings in two different studies: the original dataset (Study A), and which applied EBA (Study B). Not all methods were able to be applied as the data and activity were different. However, the reproducibility was far higher than we expected. This research contributes to expanding the reuse of analysis methods for small-scale systems such as EBA, which have not usually been reused, and further development in Learning Analytics.